Analisis Resiliensi Akademik Siswa Fatherless Di Kelas Tinggi Sekolah Dasar - Nurjamaludin, Muhammad; Rahman, Maulida Aulia; Muslihat, Neni Nadiroti; Nugraha, Widdy Sukma; Khotimah, Siti Nurul; Maharani, Balqis (Social, Humanities, and Educational Studies (SHES): Conference Series, 2025)
The research was conducted because of the high number of cases of children experiencing the absence of a father figure, both physically and psychologically, especially in Indonesia. This study aims to analyze the academic resilience experiences of fatherless students in the upper grades of elementary school. The method used is a qualitative case study with the subjects being fatherless students, 5th and 6th-grade teachers, and student parents. Data was collected through semi-structured interviews and documentation. The research results indicate that students exhibit differences in building their academic resilience through perseverance, openness to seeking help, and varying ways of managing negative emotions. The main supporting factors are the roles of mothers, teachers, and a supportive social environment. This research is expected to serve as a reference for educators and parents in supporting fatherless students.Penelitian dilakukan karena banyaknya kasus anak yang mengalami ketiadaan peran ayah secara fisik maupun psikologis terutama di Indonesia. Penelitian ini bertujuan untuk menganalisis pengalaman resiliensi akademik siswa fatherless di kelas tinggi sekolah dasar. Metode yang digunakan adalah studi kasus kualitatif dengan subjek siswa fatherless, guru kelas V dan VI, serta orang tua siswa. Data dikumpulkan melalui wawancara semi terstruktur dan dokumentasi. Hasil penelitian menunjukkan bahwa siswa menunjukkan adanya perbedaan dalam membangun resiliensi akademiknya melalui sikap pantang menyerah, keterbukaan mencari bantuan, dan cara yang berbeda dalam mengelola emosi negatif. Faktor pendukung utama adalah peran ibu, guru, dan lingkungan sosial yang suportif. Penelitian ini diharapkan menjadi rujukan bagi pendidik dan orang tua dalam mendukung siswa fatherless.